Multidisciplinary Approach to the Management of Diabetic Foot Complications - V. V. Fedyushkin; P. V. Sukhoruchkin; A. G. Baryshev; S. K. Chibirov; R. K. Amirova; D. D. Shevchuk (Инновационная медицина Кубани, 2023)
Background: According to the International Working Group on the Diabetic Foot (2015), 28 % of diabetic foot ulcers result in major amputations. Over 30 % of patients with diabetic foot undergo major amputations that result in death in 13.0 %-14.0 % of the cases.   Clinical case: In our experience of treating a female patient with diabetic foot complications, we observed that such cases require a multidisciplinary approach to determine management strategies, as well as strict surgery staging. Early plastic and reconstructive surgery demonstrated its positive impact on postoperative wound closure.   Conclusions: We managed the infection and achieved the complete closure of the major wound and primary intention healing through the multidisciplinary approach and strict adherence to surgical staging (debridement, revascularization, reconstruction). Thus, patient quality of life and rehabilitation potential significantly improved.